Evaluasi Program Kota Tanpa Kumuh (KOTAKU) dalam Penanganan Kawasan Kumuh di Kabupaten Karo - Nasution, Ahmad Rofii; Sihombing, Sally Marisa (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
The City Without Slums Program or KOTAKU is a government program that aims to overcome poverty and create livable cities for Indonesian people, one of which is in Karo Regency. However, in reality there are still waste problems in Karo Regency and poor drainage which indicates that KOTAKU has not been realized properly. This study aims to describe and examine the evaluation realization of the KOTAKU program in dealing with slum areas in Karo District. The research method used in this research is descriptive research with a qualitative approach. The results of the research show that the implementation of KOTAKU in Karo Regency is in accordance with the predetermined plan so that it meets the indicators of effectiveness. The KOTAKU program has met the adequacy indicators where KOTAKU is a solution to the slum problem in Karo Regency, provides better access to the community, and helps the community to change habits to become more environmentally friendly. Unfortunately, the focus of the KOTAKU program is in the Kabanjahe and Berastagi areas.